CardioAtlas: deciphering the single-cell transcriptome landscape in cardiovascular tissues and diseases - Tiantongfei Jiang; Xiaoyan Jin; Yueying Gao; Weiwei Zhou; Jinyang Yu; Yongsheng Li; Juan Xu; Benzhi Cai (Biomarker Research)
Abstract Increasing scRNA-seq data in cardiovascular research have substantially improved our knowledge on the development of the cardiovascular system and the mechanisms underlying cardiovascular diseases. However, the single-cell transcriptome datasets were dispersed in literature and no resource for cardiovascular systems and diseases. Here, we constructed an organized resource CardioAtlas, which provides comprehensive analysis results for > 1,929,000 cells in 27 human data sets and > 1,088,000 cells in 39 mouse data sets. Through large-scale literature retrieval and manual annotation, we constructed 12 and 15 scRNA-seq reference atlas for common human and mouse cardiovascular systems and diseases, covering 43 and 39 cell types. In particular, CardioAtlas provides five analytic modules, including cell-type prediction, identification of marker genes, functional enrichment analysis, identification of cell-type-specific transcription regulons, and cell-cell communication analysis. In addition, users can upload scRNA-seq data for personalized analysis. CardioAtlas is available at http://bio-bigdata.hrbmu.edu.cn/CardioAtlas . CardioAtlas provides the first comprehensive and well-crafted reference atlas of cardiovascular systems and diseases and describes in detail previously unrecognized cell populations across a large number of humans and mice.